Reproduction and embryonic development in two species of squaliform sharks, Centrophorus granulosus and Etmopterus princeps: Evidence of matrotrophy? - Cotton, Charles F.; Dean Grubbs, R.; Dyb, Jan E.; Fossen, Inge; Musick, John A. (Deep-sea research. Part II, Topical studies in oceanography, 2015)
Modes of reproduction and embryonic development vary greatly among the elasmobranchs, and prior studies have suggested that the energetic toll of embryogenesis in lecithotrophic species depletes embryonic organic matter by 20% or more. Matrotrophic species experience a lesser reduction or an increase in organic matter during embryogenesis. To investigate the maternal–embryonic nutritional relationship, we measured changes in organic matter from fertilization to near-parturition in embryos of Centrophorus granulosus and Etmopterus princeps. Embryos of C. granulosus experienced a reduction of 19.5% in organic matter, while E. princeps embryos experienced a reduction of 7.7% in organic matter over the course of embryonic development, suggesting some level of matrotrophy occurs, particularly for the latter species. Uterine villi were present in both species and developed concurrently with the embryos, increasing in length and thickness while becoming progressively vascularized. Embryos of C. granulosus were dissected to track the partitioning of water, organic matter, and inorganic matter to the liver, external yolk sac, internal yolk sac, digestive tract, and evicerated body throughout development. Mating was aseasonal for both species and spatially-mediated segregation by sex and maturity stage was observed. Ovarian cycles were concurrent for C. granulosus and consecutive for E. princeps. Size at maturity for C. granulosus was determined to be 111cm TL for males and 143cm TL for females, with an average fecundity of 5.3 embryos (range=4–7). Size at maturity for E. princeps was determined to be 56.5cm TL for males and 61cm TL for females north of the Azores and 54cm TL for males and 69cm TL for females near the Charlie Gibbs Fracture Zone. Average fecundity was 11.2 embryos (range=7–18) for this species. This is the first reporting of reproductive parameters for these two species, and the information provided will be valuable for informing stock assessment models in areas where these species are fished.